Wireless Mobile Robot Control With Tablet Computer - Ersahin, Gonca; Sedef, Herman (ELSEVIER SCIENCE BV, 2015)
In this study, a mobile robot carrying an on board camera is designed and implemented, which can be controlled remotely with wireless technology. Android operating system based tablet computers (controller) control mobile robot remotely and one android interface program is designed for remote control. Mobile robot is a microcontroller based embedded system and its hardware works on Linux operating system. Mobile robot and controller communicate with Wi-Fi (Wireless Fidelity) communication (socket communication). Mobile robot's camera takes video continuously and sends it to controller screen. These video contents are examined by the controller user; speed and direction information are entered from touch screen and these information are sent to mobile robot. In this manner, mobile robot movement is provided. Mobile robot motion is handled by direct current (DC) motors controlling and it is achieved with Pulse Width Modulation (PWM) method. System consists of two interrelated systems. One interrelated system is mobile robot part and the other is controller part. Mobile robot works as a server and controller works as a client. Observed video, which are taking from on board web camera, send from server to client wirelessly. Client takes video and shows it on screen. User can control the mobile robot by setting direction and speed from android tablet. Entered information sent to server and server sets motion parameters by using this information. Real-time video transportation is achieved with Motion Joint Photographic Experts Group (MJPEG) on Linux operating system. Because of the system performance, captured video is not saved. In client side (controller), speed is arranged 0 to 100 and for motion, user can set direction to left, right and direct. On controller application screen, user can see entered speed and direction values by the animated images. (C) 2015 The Authors. Published by Elsevier Ltd.
Keywords: Android; Socket Communication; Wireless Communication; Pwm; Mjpeg; Business & Economics